Sources and levels of copper and manganese supplementation influence performance, carcass traits, meat quality, tissue mineral content, and ileal absorption of broiler chickens - Groff-Urayama, Priscila M. [UNESP]; Cruvinel, Jessica M. [UNESP]; Oura, Cássio Y. [UNESP]; dos Santos, Tatiane S. [UNESP]; de Lima-Krenchinski, Fernanda K. [UNESP]; Batistioli, Julianna S. [UNESP]; Rodrigues, Paola A.D. [UNESP]; Augusto, Karolina V.Z.; Han, Yanming; Sartori, José Roberto [UNESP] (Elsevier, 2023)
This study was conducted to evaluate the effects of different levels and sources of Cu and Mn (sulfate or hydroxychloride - H) on growth performance, carcass traits, meat and skin quality, footpad dermatitis severity, litter quality, liver and plasma mineral content, and ileal mineral absorption. A total of 1,920 one-day-old male Cobb 500 broiler chicks were assigned randomly to one of 2 × 3+2 factorially arranged treatments: CuH (15 and 150 ppm) × MnH (40, 80, 120 ppm) + 15 ppm Cu Sulfate with 80 ppm Mn Sulfate (control 1) or 150 ppm Cu Sulfate with 120 ppm Mn sulfate (control 2) for 42 d. Each treatment consisted of 8 replicates of 30 birds. At 42-day-old were slaughtered for carcass yield and meat quality analyses. At 43-day-old, it was determined the apparent ileal absorption of minerals and the concentration of Cu and Mn in the liver and plasma. The resistance and elasticity of the skin, and footpad dermatitis severity were also evaluated. The level 150 ppm CuH improved the FCR compared to the 15 ppm CuH and 15 ppm Cu Sulfate level. Broilers fed diets containing 150 ppm CuH showed higher breast yield compared to those fed diets containing 15 ppm. Breast yield was positively influenced by the inclusion of 40 ppm MnH. There was an interaction between the CuH and the MnH for skin elasticity, and the highest elasticity was found when the supplementation levels were 150 ppm CuH and 40 ppm MnH. High levels of copper decreased the incidence of footpad dermatitis. The hydroxychloride source determined a higher mineral concentration in the liver and plasma and greater apparent ileal absorption of Cu and Mn. In conclusion, dietary supplementation with 150 ppm CuH and 40 or 80 ppm MnH enhance breast yield and improves skin resistance. The inclusion of 150 ppm CuH has the possibility to improve the FCR and decrease leg injuries. Furthermore, the hydroxychloride source seems to be more bioavailable than the sulfate source.
Keywords: bioavailability; hydroxychloride; inorganic source; poultry nutrition; trace minerals